Genomic and Bioinformatic Characterization of Mouse Mast Cells (P815) Upon Different Influenza A Virus (H1N1, H5N1, and H7N2) Infections - Huo, Caiyun; Wu, Hongping; Xiao, Jin; Meng, Di; Zou, Shumei; Wang, Ming; Qi, Peng; Tian, Haiyan; Hu, Yanxin (Frontiers in Genetics, 2019)
Influenza A virus (IAV) is a segmented negative-stranded RNA virus that brings a potentially serious threat to public health and animal husbandry. Mast cells play an important role in both the inherent and adaptive immune response. Previous studies have indicated that mast cells support the productive replication of H1N1, H5N1, and H7N2. To date, the distinct molecular mechanism behind the pathogenesis in mast cells among the three different viruses has been poorly understood. In this study, we investigated the genomic profiles in detail and the dynamic change of genomes regulated by different subtypes of IAV in mouse mast cells using microassays. Compared with any two of the three IAV-infected groups, many more differentially expressed genes (DEGs), cellular functions, and signaling pathways were confirmed in H1N1 or H7N2 group, with the H7N2 group showing the highest levels. However, few DEGs were detected and various cellular functions and signaling pathways were dramatically suppressed in the H5N1 group. With an in-depth study on the H1N1 and H7N2 groups, we demonstrated the essential role of the 5-HT signaling pathway and the cyclic guanosine monophosphate (cGMP)/protein kinase G (PKG) signaling pathway, which were preferentially activated in P815 cells infected by H1N1, and the crucial role of the HIF-1 signaling pathway that was preferentially activated in P815 cells infected by the H7N2 virus. Furthermore, real-time quantitative polymerase chain reaction (RT-qPCR) results showed significantly increased mRNA levels of 5-HT and PKG in H1N1-infected P815 cells and increased HIF-1 in H7N2-infected P815 cells. In addition, exosomes were preferentially secreted from H1N1-infected or H7N2-infected P815 cells and are potentially pivotal in innate immunity to fight IAV infection. This study provides novel information and insight into the distinct molecular mechanism of H1N1, H5N1, and H7N2 viruses in mast cells from the perspective of genomic profiles.